Pengaruh Kebijakan Dividen dan Struktur Modal Terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Aisy, Rihhadatul; Taqwa, Salma (Universitas Negeri Padang, 2025)
This research aims to prove and analyze the influence of dividend policy and capital structure on manufacturing sector companies on the Indonesia Stock Exchange. In this research, the samples were 26 manufacturing companies in the consumption sub-sector on the Indonesian Stock Exchange. The data used is from 2019 to 2023. The information and data used in this research is secondary data obtained through literature study via the IDX website and the websites of each company selected as a sample. The analytical method used in this research is multiple linear regression and t-statistical testing. In accordance with the results of testing the first hypothesis, it was found that dividend policy had a positive effect on the performance of manufacturing companies on the Indonesia Stock Exchange in 2019 - 2023, while in the second hypothesis testing stage it was found that capital structure had a negative effect on the performance of manufacturing companies in 2019 - 2023.